Carbohydrate Concentration in Lentils (Lens culinaris Medikus.): Genotypic and Environmental Effects. Issue 20 (13th November 2017) - Graham, Christopher; Thavarajah, Dil; Beck, Ruth
ABSTRACT: Lentils contain a range of prebiotic carbohydrates; however, genotypic and environmental implications of these components have not been well understood. The objective of this study was to determine the genetic and environmental variation of carbohydrate concentrations in three commonly grown lentil cultivars in South Dakota, USA at two locations over two growing seasons. Significant genetic and environmental variation was found for most of the constituents evaluated. Raffinose-family oligosaccharides (RFO) ranged from 3161 mg 100g −1 at Bison and 3670 mg 100g −1 at Wall and from 3217 mg 100g −1 to 3650 mg 100g −1 between cultivars. Moreover, RFO content was strongly correlated to a simple plant stress index (SI) in which higher estimated plant stress (e.g., low precipitation) produced higher levels of RFO. These results demonstrate important differences in prebiotic concentrations, which can be used for future lentil breeding efforts when matching cultivars to diverse growing climates with highly variable growing season precipitation.